EPIDEMIOLOGICAL PROFILE OF VIRAL HEPATITIS IN GOIÁS (2019–2023) IN COMPARISON WITH THE NATIONAL TREND (CIPEEX, 2025)
INTRODUCTION: Viral hepatitis represents a significant public health concern in Brazil due to its high prevalence, risk of chronic progression, and association with severe outcomes such as liver cirrhosis and hepatocellular carcinoma. These infections, often silent in most cases, substantially contribute to the global burden of liver diseases. Epidemiological surveillance is essential to guide screening, vaccination, early diagnosis, and the provision of appropriate treatment. In 2023, the state of Goiás stood out nationally for the marked increase in notifications, in contrast to the stability observed in the rest of the country. OBJECTIVE: To describe the epidemiological profile of viral hepatitis in Goiás between 2019 and 2023, based on DATASUS/SINAN data, and to compare it with the national trend during the same period. METHODOLOGY: Observational, descriptive, retrospective study based on the analysis of secondary data extracted from SINAN through the TABNET/DATASUS platform, accessed in July 2025. Confirmed cases in Goiás were evaluated according to year of diagnosis, age group, and macro-region of residence, followed by comparison with national data. The analysis included calculation of absolute and relative frequencies as well as percentage variations, in order to identify regional and temporal patterns. RESULTS: Goiás reported 3,430 cases of hepatitis B and C during the study period, with a similar distribution between HBV (49.2%) and HCV (50.8%). An increase in HCV detection rates and a decline in HBV cases were observed. The most affected age groups were 40–59 years and 20–39 years. The Central-West macro-region accounted for most cases. Nationally, notifications remained stable, ranging from 35,000 to 37,000 cases per year. CONCLUSION: The divergent pattern observed in Goiás suggests intensified testing, expanded screening initiatives, or improvements in notification processes. The findings reinforce the importance of active surveillance, early diagnosis, vaccination coverage, and treatment access as strategic pillars in the control of viral hepatitis.
Keywords: Viral Hepatitis; Public Health; Epidemiological Surveillance